2021
DOI: 10.3390/v13071222
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Analgesia with Tramadol in the Coxsackievirus B3 Myocarditis Mouse Model

Abstract: Infection of mice with Coxsackievirus B3 (CVB3) triggers inflammation of the heart and this mouse model is commonly used to investigate underlying mechanisms and therapeutic aspects for viral myocarditis. Virus-triggered cytotoxicity and the activity of infiltrating immune cells contribute to cardiac tissue injury. In addition to cardiac manifestation, CVB3 causes cell death and inflammation in the pancreas. The resulting pancreatitis represents a severe burden and under such experimental conditions, analgesic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Reported numbers were normalized for the utilized tissue weight, yielding the number of cells per milligram of tissue. For heart tissue, the following cell subsets were defined based on the gating procedure shown by Pinkert et al 43 : macrophages: CD45 + CD11b + B220 − CD3 − NK1.1 − Ly6G[1]CD11c +/− F4/80 + , inflammatory monocytes: CD45 + CD11b + B220 − CD3 − NK1.1 − Ly6G − CD11c − F4/80 − Ly6C hi , stationary monocytes: CD45 + CD11b + B220 − CD3 − NK1.1 − Ly6G − CD11c − F4/80 − Ly6C low , neutrophils: CD45 + CD11b + B220 − CD3 − NK1.1 − Ly6G + SSC hi , dendritic cells: CD45 + CD11b + B220 − CD3 − NK1.1 − Ly6G − CD11c + F4/80 − MHCII + , B cells: CD45 + CD11b − B220 + CD3 − , T cells: CD45 + CD11b − B220 − CD3 + .…”
Section: Methodsmentioning
confidence: 99%
“…Reported numbers were normalized for the utilized tissue weight, yielding the number of cells per milligram of tissue. For heart tissue, the following cell subsets were defined based on the gating procedure shown by Pinkert et al 43 : macrophages: CD45 + CD11b + B220 − CD3 − NK1.1 − Ly6G[1]CD11c +/− F4/80 + , inflammatory monocytes: CD45 + CD11b + B220 − CD3 − NK1.1 − Ly6G − CD11c − F4/80 − Ly6C hi , stationary monocytes: CD45 + CD11b + B220 − CD3 − NK1.1 − Ly6G − CD11c − F4/80 − Ly6C low , neutrophils: CD45 + CD11b + B220 − CD3 − NK1.1 − Ly6G + SSC hi , dendritic cells: CD45 + CD11b + B220 − CD3 − NK1.1 − Ly6G − CD11c + F4/80 − MHCII + , B cells: CD45 + CD11b − B220 + CD3 − , T cells: CD45 + CD11b − B220 − CD3 + .…”
Section: Methodsmentioning
confidence: 99%
“…The mice were killed, and heart tissue was taken and fixed in 10 % formaldehyde solution. After dehydration, washing, and embedding in paraffin to prepare pathological sections, the implanted hearts were cut into 5 μm sections and stained with hematoxylin and eosin (H&E) (5) .…”
Section: Methodsmentioning
confidence: 99%
“…In addition to direct virus-induced cardiac cytotoxicity, the immune system and host genetics play a central role in myocardial inflammation (4) . An immune response is necessary to control the virus, but inflammatory processes lead to cardiac damage and fibrotic remodeling (5) . Toll-like receptors (TLRs) are a class of innate immune recognition receptors that recognize molecular patterns associated with microorganisms and induce immune responses (6) .…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 Nevertheless, in recent work unrelated to the ISG15 field, we and others demonstrated that systemic pathology with haemodynamic compromise and weight loss during CVB3 infection is, if at all, only marginally attributable to viral cytotoxicity and inflammatory damage responses in heart tissue. 9 , 10 CVB3 infection of the heart induces small inflammatory foci, while the vast majority of cardiomyocytes, as well as systolic function of the ventricle, remain intact. 9 Therefore, it remains unclear if and to what extent the virus-suppressive activity of ISG15 attributes to maintained cardiac performance during CVB3 infection of mice.…”
Section: Introductionmentioning
confidence: 99%